50 Womens' verdicts on consequences and labelling of gestational diabetes: a community jury. (4th December 2019) - Thomas, Rae; Scott, Anna; Sims, Rebecca; Craig, Louise; Claase, Leigh-Anne; Lowe, Julia; Heal, Clare; Hardiman, Leah; Glasziou, Paul
Abstract : Objectives: Women diagnosed with gestational diabetes mellitus (GDM) are potentially at increased risk for physical complications such as increased rates of caesarean sections, large babies, and babies with shoulder dystocia and low blood sugar. Diagnosis may offer opportunities to change behaviours yet emotional harms such as high levels of anxiety and social exclusion are widely reported by women. There is no international agreement about the testing process or the appropriate threshold of blood glucose for GDM diagnosis. In 2015, Australia adopted a new, recommended definition and testing procedure for GDM, in the absence of national consensus. Significant increases in the number of women diagnosed with GDM have been reported but with little difference in health outcomes. We explored the values and preferences of the women who may be impacted by a GDM diagnosis. Method: We aimed to recruit 15 women from the Gold Coast region (Australia) and rural areas within driving distance to the Gold Coast. Eligible women were between 30 and 45 years old, had had at least one pregnancy, and no previous diagnosis of GDM. The CJ was conducted over two weekend days, 2 nd and 3 rd February 2019, at Bond University. Four expert presentations were conducted using voice-over powerpoint. Topics were: what is GDM, its diagnosis and treatment options; a brief history of definition changes: the Australian context; and potential consequences of GDM. Opportunity to question the experts was provided on both days. The jurors were asked to provide recommendations to two questions. In the jury's view, which important consequences of a diagnosis of GDM should be considered by the consensus panel when discussing the Australian definition of GDM? What should Australian health practitioners call the health condition currently known as GDM? Results: 116 women were contacted for 15 women to consent. Of those, 8 attended from urban and a rural setting: 3 failed to confirm and didn't attend; 3 confirmed participants failed to attend, 1 didn't attend due to illness. Participants' recommendations were a consensus. Women were surprised that the level of risk for physical harms was low but emotional harms were high. Despite initially prioritising the baby's needs, after an improved understanding of risks, women changed their preferences. The final ranking of important consequences in order of high to low importance was: negative emotions experience by women; the burden of managing GDM; over-medicalised pregnancy; opportunity to minimise the risks to the baby; opportunity to improve lifestyle; and macrosomia. To describe the four different clinical states of GDM, and to minimise the potential harms of the GDM diagnostic label, the jurors chose three different labels. Only one was GDM. Conclusions: Clinicians report that anecdotally, women diagnosed with GDM will always put their babies needs before their own. Although smaller than anticipated, this CJ demonstrated that a group of women informed about the evidence of likelihood of the potential consequences of GDM, recognised the negative emotional consequences to themselves was of greatest concern. The current glucose threshold for GDM in Australia is set at a cut-point for an adverse risks including macrosomia and neonatal hyperinsulemia. When informed about the level of risk to women and babies, the CJ participants ranked macrosomia as the last priority. Only one of the eight women identified macrosomia as an important risk. It is essential we reconsider how new definitions of diseases are made, as clinicians do not attribute women's priorities accurately, nor do they ask informed women. It is time for community voices impacted by these decisions to be embedded in the decision-making.